The effect of training on mitochondrial mitophagy factors in obese male rats - Mozhgan Ahmadi; Neda Aghaei Bahman Begloo (Shahid Beheshti University, 2022)
purpose: Mitophagy can assist in mitochondrial quality control. The aim of this study was to investigate the effect of training on mitochondrial mitophagy factors in obese male rats.Methods: In this experimental study, 40 male rats (weight 120 ± 20 g) after inducing obesity with high fat diet (for 10 weeks), eight rats from the high-fat diet group (O) and eight rats of the standard dietary group (C) to investigate the induction of obesity were described and other obese rats were randomly divided into three groups: obesity control (OC), moderate intensity continuous training (MICT) and high intensity interval training (HIIT). The HIIT protocol includes 10 bouts of 4-minute activity with intensity of 85-90% vo2max and 2-minute active rest periods and MICT protocols performed five sessions per week, with intensity of 65-70% VO2max for 12 weeks. Bcl2 and parkin levels were measured by gel electrophoresis and western blotting. Data were analyzed by One-way ANOVA and post hoc Tukey at P ≤ 0.05.Results: The results showed that both HIIT and MICT training significantly increased bcl2 and PARKIN of Soleus muscle in comparison with the control group (P < 0.05). However, there was no significant difference between the two groups of HIIT and MICT in bcl2 and PARKIN levels of Soleus muscle in obese male rats (P > 0.05).Conclusion: According to the results, it seems that HIIT and MICT can help reduce mitochondrial degradation and impairment in skeletal muscle during obesity.